Liberalism in Education and Employment Opportunities: A Reflection on Higher Learning Education and Actual Labour Market in Tanzania - Mtallo, Godson Robert; Churk, Josephine Philip (Indonesian Journal of Social Research (IJSR), 2026)
This study examines the alignment between higher learning education and the labour market in Tanzania. The shift from a socialist ideology to a free-market economy, coupled with technological advancements and increased competition in the East African community, has led to a scarcity of employment opportunities. The current education system needs to adapt to the changing needs of the workforce and foster self-reliance and creativity. The study aims to assess the influence of liberalism in education and employment opportunities in higher learning education in Tanzania. Specifically, the study evaluates the alignment of higher learning institutions' curricula with employment opportunities in Tanzania. The study utilizes a mixed research approach, including a survey of graduates. The findings reveal the skills gap in the higher learning education curriculum in employment opportunities in Tanzania. The findings contribute to evidence-based strategies and policies that improve graduates' employability and success in the labour market. The study concludes that higher learning institutions should provide appropriate training to enable graduates to acquire employment skills. Also, the government should address the unemployment situation of graduates in the country by investing in projects that offer youths employment.